STUDI PUSTAKA: PENGARUH EVAPOTRANSPIRASI TERHADAP MIKROKLIMAT DAN IMPLIKASINYA TERHADAP PENGENDALIAN ORGANISME PENGGANGGU TANAMAN (AGRO TATANEN | Jurnal Ilmiah Pertanian, 2026)
Evapotranspiration (ET), the combined process of evaporation from the soil surface and transpiration from plants, plays a crucial role in forming the microclimate around vegetation. This microclimate significantly influences humidity, temperature, and leaf wetness duration, which are key factors in the dynamics of Plant Pest Organisms (PPOs), such as pests and pathogens. This study aims to examine the relationship between evapotranspiration and the microclimate and its implications for PPO control. The method employed is a literature review, analyzing various relevant journals and scientific sources published within the last ten years. The findings indicate that managing evapotranspiration through techniques such as precision irrigation, selecting appropriate plant varieties, regulating planting distance and timing, controlling shading, ecological engineering and refugia utilization, and employing remote sensing and microclimate sensor technology can suppress excessive humidity that supports PPO development. This approach is not only relevant for PPO control but also supports water use efficiency and climate change adaptation. This review is expected to contribute to the development of ecology- and technology-based sustainable agriculture strategies, particularly in addressing future food production challenges. As a recommendation, integrating ET strategies into Integrated Pest Management (IPM) systems supported by spatial data and artificial intelligence (AI) should be gradually implemented at small scales, with collaborative involvement of researchers, extension agents, and farmers to ensure both technical effectiveness and socioeconomic relevance in tropical agricultural contexts.